Portable Cardiac Mapping Assessment of Acute Ischaemic Injury - Anderson, J. McC.; Dempsey, G. J.; Wright, G. T. H.; Cullen, C.; Crawley, M.; McAdams, E. T.; McLaughlin, J.; MacKenzie, G.; Adgey, A. A. J. (Methods of Information in Medicine, 1994)
A portable cardiac mapping system is used to improve the accuracy of diagnosis of acute ischaemic injury outside hospital. Patients presenting chest pain suggestive of myocardial infarction (Ml) were mapped by attendant medical personnel operating from a mobile coronary unit. These first Ml maps were compared against average normal maps using QRS and ST-T isointegral values. Discriminant function analysis performed on the parameters achieved a sensitivity of 90% and a specificity of 96%.
Keywords: Cardiac Mapping; Ischaemic Injury; Isointegrals; Discriminant Function Analysis